Telemedicine applied to plastic surgery: an integrative review - Kênya de Souza Borges; Valter Oberdan Borges de Oliveira; João Batista Cavalcante Filho; Sílvia de Magalhães Simões; Adicinéia Aparecida de Oliveira; Carlos Anselmo Lima (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: Telemedicine refers to providing medical services through information technology and communication between patients and service providers. Plastic surgery is a field especially favorable to the application of telemedicine since visual inspection of the patient guides both diagnosis and clinical follow-up. Methods: An integrative review was performed in the articles published in telemedicine in plastic surgery in the PubMed database, using the terms MeSH: "telemedicine" AND "plastic surgery." After tracking and applying eligibility criteria, the remaining articles' full text were digitized, with their data extracted for detailed analysis. Results: A total of 134 articles were identified, all in English, in the initial search for PubMed. After screening and application of the exclusion criteria, 12 studies were included for the integrative review. The articles found in this review demonstrated benefits in the use of telemedicine applied to plastic surgery. Especially in the postoperative follow-up of patients, in the reduction or extinction of the need for face-to-face visits, in the satisfaction of patients in the consultations carried out by telemedicine, in the reduction of financial costs and response time for referrals, in the diagnostic accuracy similar to the face-to-face assessment and in improving access to specialized care in remote places, both geographically and socially unfavorable. Four articles discussed barriers and limitations, observed or potential, to the use of telemedicine in plastic surgery, such as data security, legislation, costs and perception of negative influence on doctor-patient communication. Conclusion: The analyzed studies show an expressive gain in knowledge about telemedicine applied to plastic surgery in recent years.